Effect of different photoperiods on the biology of immatures and adults of Anopheles darlingi (Diptera: Culicidae) - Nonato Dos Santos, Amanda; Tavares Trindade, Frances Tatiane; de Almeida e Silva, Alexandre (Revista Colombiana de Entomología, 2023)
Studies on the mosquito Anopheles darlingi Root (Diptera: Culicidae) are essential since it is the main vector of human malaria in the Brazilian Amazon. Photoperiod affects several biological variables of mosquitoes including motor, e.g., mating behavior, and oviposition and behavioral, e.g., consuming sugar and blood diets, activities, therefore, this work investigated the effect of different photoperiods on the biology of this species. Mosquitoes were reared under three different treatments: (i) 12 L:12 D, (ii) 24 L:0 D (constant light), and (iii) 0 L:24 D (constant darkness). Fifty larvae per tray were reared under different light periods and fed ground fish food. Survival and larval development times, emergence and pupation rates, the male-to-female ratio, and adult longevity were recorded. The use of different photoperiods affected several biological parameters of A. darlingi. The 24 L:0 D and 0 L:24 D treatments resulted in higher mortality, whereas constant light increased larval development time. The male-to-female ratio was greatly reduced under constant light conditions, but adult longevity was not affected by the photoperiods used. Thus, unnatural light conditions (complete light or complete darkness) result in suboptimal mosquito rearing.